Correction: Anti-ulcerogenic effect of KFP-H008 against ethanol-induced gastric ulcer via p38 MAPK/NF-κB pathway. Issue 31 (4th June 2019) - Su, Mei; Li, Cheng-yuan; Zhou, Lin; Yan, Yun-yi; Ao, Lu-yao; Wang, Guang-ji; Fang, Wei-rong; Li, Yun-man
Abstract : Correction for 'Anti-ulcerogenic effect of KFP-H008 against ethanol-induced gastric ulcer via p38 MAPK/NF-κB pathway' by Mei Su et al., RSC Adv., 2017, 7, 49423–49435.